2006
DOI: 10.1051/0004-6361:20054394
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of Hickson compact groups and of the loose groups within which they are embedded

Abstract: Using new data and an enlarged group sample we verify some of our previously published results and present a number of new facts that suggest that compact groups could be casual concentrations in prolate-like looser groups, and thus the nature of compact and ordinary poor groups is probably the same. To this end we used the Sloan Digital Sky Survey (SDSS) redshift catalogue to look for galaxies with accordant redshifts in the nearby environment (up to ∼2 Mpc) of 15 Hickson compact groups (HCG). We also used kn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 75 publications
(116 reference statements)
1
21
0
Order By: Relevance
“…Therefore, at least some X-rayYluminous, intermediate-redshift groups have central densities comparable to CGs. This result is consistent with the observation that many CGs at low redshift are actually associated with larger galaxy systems (Ramella et al 1994;Barton et al 1996;de Carvalho et al 1997;Ribeiro et al 1998;Tovmassian et al 2006). This is also consistent with the fact that many CGs are luminous in X-rays, although typically with lower luminosities than the groups studied here (Ponman et al 1996).…”
Section: Brightest Group Galaxiessupporting
confidence: 92%
“…Therefore, at least some X-rayYluminous, intermediate-redshift groups have central densities comparable to CGs. This result is consistent with the observation that many CGs at low redshift are actually associated with larger galaxy systems (Ramella et al 1994;Barton et al 1996;de Carvalho et al 1997;Ribeiro et al 1998;Tovmassian et al 2006). This is also consistent with the fact that many CGs are luminous in X-rays, although typically with lower luminosities than the groups studied here (Ponman et al 1996).…”
Section: Brightest Group Galaxiessupporting
confidence: 92%
“…To do this, we have compiled in (Koda et al 2015), the velocity dispersion was taken from Girardi et al (1993), whereas for the Fornax cluster (Muñoz et al 2015) the velocity dispersion is obtained from Drinkwater et al (2001). Finally, for the groups presented in this paper, we have used the velocity dispersions given by Tovmassian et al (2006). Once we have the velocity dispersions, we follow Munari et al (2013) to get M 200 for these structures.…”
Section: The Abundance Of Udgs As a Function Of The Halo Massmentioning
confidence: 99%
“…Brasseur et al (2009) found that only 30 per cent of the simulated groups are truly compact in three dimensions, which will lead to biases in any observational study unable to infer this lack of compactness. An even more radical scenario was proposed by Tovmassian et al (2006), who claimed that CGs are no different from LGs. However, the general consensus is that a significant fraction of the compact groups with accordant-velocity members are physically dense systems.…”
Section: Introductionmentioning
confidence: 99%